2002
DOI: 10.1080/003655202317316088
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Grass Juice in the Treatment of Active Distal Ulcerative Colitis: A Randomized Double-blind Placebo-controlled Trial

Abstract: Wheat grass juice appeared effective and safe as a single or adjuvant treatment of active distal UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
110
0
8

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(118 citation statements)
references
References 11 publications
0
110
0
8
Order By: Relevance
“…In line with folk sayings, the health benefits of wheatgrass may include improved digestion, blood pressure reduction, heavy metal detoxification from the bloodstream, immune system modulation, and gout alleviation. Several papers have indicated that wheatgrass has anti-tumor activities (1), anti-oxidant properties (2), and a therapeutic effect on distal ulcerative colitis (3). In addition, wheatgrass may help prevent some disorders, including diabetes and heart disease (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In line with folk sayings, the health benefits of wheatgrass may include improved digestion, blood pressure reduction, heavy metal detoxification from the bloodstream, immune system modulation, and gout alleviation. Several papers have indicated that wheatgrass has anti-tumor activities (1), anti-oxidant properties (2), and a therapeutic effect on distal ulcerative colitis (3). In addition, wheatgrass may help prevent some disorders, including diabetes and heart disease (4).…”
mentioning
confidence: 99%
“…Therefore, we integrated combinatorial detection of surface markers with cytomic screening to examine immunity-related bioactivity and hunt for immunomodulatory compounds from natural extracts (15). For systematic screening, hPBMCs 3 were used as the cell model to * This work was supported by the National Science Council, Development observe the phenotypic changes and describe the immune modulation properties of wheatgrass.…”
mentioning
confidence: 99%
“…Wheatgrass juice stimulates the immune system of normal and predsinolone-treated Swiss albino mice 5 . Furthermore, wheatgrass juice is an effective treatment in clinical trials of active distal ulcerative colitis 22 and prevents myelotoxicity from chemotherapy in breast cancer patients 23 . Additionally, extracts from wheat sprouts grown over a period of 3-5 days inhibit the mutagenic activity of benzo[a]pyrene in rats.…”
Section: Discussionmentioning
confidence: 99%
“…We chose to study this type of diet because it has been described as beneficial in some anecdotal reports (13) and because each of its components is reported to have health benefits. (18)(19)(20) …”
Section: Introductionmentioning
confidence: 99%